In-silico study of the ionic current gradients determining left-to-right atrial frequencies during paroxysmal atrial fibrillation. (December 2019) - Palacio, Laura C; Ugarte, Juan P; Tobón, Catalina
Atrial fibrillation is the most prevalent cardiac arrhythmia. Paroxysmal atrial fibrillation (pAF) may occur in episodes lasting from minutes to days. Recent studies suggest that some pAF episodes present a left-to-right dominant frequency gradient caused by ionic current gradients. However, how each ionic current gradient affects the left-to-right dominant frequency gradient during pAF has not been studied. In this work, we use a 3D model of human atria to study how the ionic current gradients affect the dominant frequency gradient during pAF induced by continuous ectopic activity. The role of the specific gradients of acetylcholine-activated potassium current ( I KACh ) and inward-rectifier potassium current ( I K1 ) on determining the left-to-right dominant frequency gradient was assessed. The main outcome of this study is that either or both of the I KACh or I K1 gradients are necessary to induce a left-to-right dominant frequency gradient during pAF. However, both gradients are necessary to the left atrium maintaining, by itself, the pAF episode. These findings have potentially important implications for the development of atrial-selective therapeutic approaches.